Analysis of the Impact of National Strategic Infrastructure Development (Trans-Sumatra Toll Road) on Changes in Spatial Patterns and Accessibility in North Labuhanbatu Regency - Robin Panjaitan; Cut Nuraini; Abdi Sugiarto (CV. Doki Course and Training, 2026)
The development of the trans-sumatra toll road, particularly the rantau prapat–kisaran section, has had a significant impact on changes in spatial patterns, accessibility, and local economic potential in north labuhanbatu regency. this study employs a descriptive qualitative approach, with data collection techniques including in-depth interviews, participatory observation, and documentation. research informants consist of affected communities, policymakers, and local business actors. the results indicate that toll road development has led to land-use conversion from agriculture to residential, industrial, and commercial uses, as well as changes in settlement patterns and the distribution of economic activities. improved accessibility generated by the toll road and supporting facilities, such as aek kanopan terminal, has accelerated population mobility and goods distribution, reduced logistics costs, and expanded market reach. moreover, this infrastructure development has stimulated local economic growth by increasing agricultural sector income and creating new trade opportunities. overall, the development of the toll road and its supporting infrastructure is generally aligned with the spatial plan (rtrw) of north labuhanbatu regency, although continuous monitoring is required to maintain spatial balance and prevent land-use conflicts. this study provides important insights for sustainable infrastructure development planning in north sumatra.